Insan Kamil-Based Development to Improve Character and Academic Competency in Indonesian Islamic Universities - Sumanta Sumanta (UIN Sultan Aji Muhammad Idris Samarinda, 2022)
Higher education plays an important role in shaping future leaders. Therefore, it is necessary to pay attention to the quality of graduate students because they will participate in determining the progress of the nation. This study aims to examine the factors that influence the quality of graduates in Islamic-based universities in Indonesia, including character development, academic competence, understanding of human beings, and awareness of good morals. This research is a quantitative method that is operationalized through a survey approach to 100 Islamic college students and analyzed through SEM-PLS. The results of the study show that only the understanding of human beings and the awareness of good morals have a significant influence on the quality of graduates from Islamic universities in Indonesia. While the development of character and academic competence does not affect the quality of graduates of Islamic universities in Indonesia. This finding implies that when the government wants to improve the quality of Islamic tertiary education graduates in Indonesia, the factors that need to be improved are the understanding of human beings and awareness of the good character of Islamic college students.